Creative and adaptive sports learning model to increase participation of students with special needs - Setiya Yunus Saputra; Frendy Aru Fantiro; Vivi Kurnia Herviani; Abdurrohman Muzakki; Reza Fauzan Akbar (Universitas Muhammadiyah Malang, 2024)
This study aims to develop and test the effectiveness of a creative and adaptive sports learning model in increasing the participation of students with special needs. The study used an experimental quantitative approach involving 30 students with special needs in an inclusive elementary school. Data were collected through participant observation, structured interviews with teachers and therapists, and questionnaires to parents, after which the data were analyzed using descriptive and inferential statistical techniques. Descriptive statistical analysis showed an average student participation of 86.94 after the implementation of the learning model, which showed a significant increase. The Wilcoxon Signed Ranks Test inferential test also showed a significant difference (p<0.05) between student participation before and after the implementation of the model. The results of interviews with parents revealed a positive impact not only on the physical aspects, but also the social and emotional aspects of their children. Adjustments to equipment, environment, and sports methods allowed students with special needs to be more actively involved in physical activities. These findings support the principles of inclusive education and indicate that the creative and adaptive learning model is effective in creating an inclusive learning environment. This study recommends the implementation of the model in other inclusive schools to increase the participation of students with special needs and support their holistic development.